Structure of the outer membrane porin OmpW from the pervasive pathogen Klebsiella pneumoniae - Seddon,C; Frankel,G; Beis,K (Acta Crystallographica Section F: Structural Biology and Crystallization Communications Online, 2024)
Conjugation is the process by which plasmids, including those that carry antibiotic-resistance genes, are mobilized from one bacterium (the donor) to another (the recipient). The conjugation efficiency of IncF-like plasmids relies on the formation of mating-pair stabilization via intimate interactions between outer membrane proteins on the donor (a plasmid-encoded TraN isoform) and recipient bacteria. Conjugation of the R100-1 plasmid into Escherichia coli and Klebsiella pneumoniae (KP) recipients relies on pairing between the plasmid-encoded TraNα in the donor and OmpW in the recipient. Here, the crystal structure of K. pneumoniae OmpW (OmpWKP) is reported at 3.2Å resolution. OmpWKP forms an eight-stranded β-barrel flanked by extracellular loops. The structures of E. coli OmpW (OmpWEC) and OmpWKP show high conservation despite sequence variability in the extracellular loops.